The Analysis of Natural Disaster Risk Impact on Labor Market Outcomes: Does It Lead to Middle-Class Workers Decrease? - Salahudin Al Ayyubi, Muhammad; Pratomo, Devanto Shasta; Prasetyia, Ferry (AIBPM Publisher, 2024)
Indonesia, as a country that is progressing towards an upper middle-income country, is facing a high incidence of disasters. Understanding how disasters impact living standards is still relatively difficult due to the lack of relevant studies in the literature. Therefore, the study aims to analyze the likelihood of individuals who were in areas with a high risk of disaster becoming middle-class workers. In this study, the incidence of disasters is represented by the disaster risk index, which comprises three components, namely the hazard, vulnerability, and capacity components in each province and regency/city based on the definition carried out by the National Disaster Management Agency (BNPB). By using logistics methods, this study found that individuals living in areas with a high risk of disaster tend to have a lower chance of becoming middle-class workers. In overcoming the labor market challenges faced by regions with high disaster risk, careful policy steps are needed that focus on strengthening capacity and reducing the risk of high investment costs. Enhancing disaster-resistant infrastructure and community networks as well as improving access to social protection services and promoting economic recovery are priorities.